Spatio-temporal and trade export risk analysis of bluetongue disease in France: A case study of China - Yang, Qiao-ling; Zhang, Shu-wen; Qiu, Song-yin; Zhang, Qiang; Chen, Qin; Niu, Bing (Frontiers in Veterinary Science, 2022)
Bluetongue disease (BT) is a viral disease that can be introduced through imported animals and animal products, affecting local animal husbandry. In this study, the spatial and temporal patterns of BT outbreaks (outbreak: a BT infection in cattle, sheep or goats on a farm, involving at least one infected animal) in France were analyzed and the risk of introducing bluetongue virus (BTV) into countries through trade were assessed. A spatiotemporal analysis of BT reported during the study period (2015-2018) showed that there were clustered outbreaks of BT in France in 2016 and 2017, with outbreaks concentrated from August to December. The outbreak moved eastward from the center of mainland France to surrounding countries. A semi quantitative risk analysis framework was established by combining the likelihood assessment and consequence analysis of introducing BTV into trading countries through trade. Exemplified by China, the research showed that in the analysis of the likelihood of BTV from France being introduced into trading countries through live cattle trade, if China imports a large number of live cattle, it will bring high risks. The likelihood of introducing the bovine semen into trading countries was similar to that of live cattle, but the harm caused by the trade in live cattle was higher than that caused by the trade in bovine semen. This risk analysis framework can provide a reference for other countries to quickly assess the risk of bluetongue transmission in import and export trade.